2010
DOI: 10.1007/s12020-010-9352-2
|View full text |Cite
|
Sign up to set email alerts
|

A patient with concurrent primary aldosteronism and Page kidney

Abstract: The ratio of aldosterone-to-renin activity is currently recommended as a screening test for primary aldosteronism (PA). There are many factors interfering the interpretation of aldosterone-renin ratio (ARR) and could hamper in-time diagnosis of PA. Here, we first report a patient with underlying Page phenomenon and an accidentally disclosed adrenal incidentaloma. High renin secretion from Page phenomenon had masked higher ARR into normal ARR obscuring the diagnosis of PA. However, adrenal venous sampling (AVS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Only 12.1% of the patients required amputation in association with osteomyelitis. The multidisciplinary approach is a key factor in decreasing reulceration and thus reducing the amputation rates, as previous studies have demonstrated 14,15. In 61.8% of the cases, the healing time was longer than 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Only 12.1% of the patients required amputation in association with osteomyelitis. The multidisciplinary approach is a key factor in decreasing reulceration and thus reducing the amputation rates, as previous studies have demonstrated 14,15. In 61.8% of the cases, the healing time was longer than 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐five patients with biochemically confirmed PA and 12 age‐matched healthy volunteers were recruited. The diagnosis of PA in hypertensive patients was made based on the confirmatory protocol provided by the TAIPAI (Taiwan Primary Aldosteronism Investigators) study group (19), which required the following diagnostic criteria: evidence of autonomous excess of aldosterone production presented as plasma aldosterone‐to‐renin activity (ARR) >35 (ng/dL per ng/mL/hr) and plasma aldosterone concentration (PAC) >10 ng/dl after either captopril or saline infusion tests. Patients with known renal dysfunction or serum creatinine over 1.8 mg/dL were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, the diagnostic algorithm can be challenging due to several factors that are known to affect the secretion of renin and aldosterone, such as medications, serum potassium, and so on [ 8 , 9 , 10 ]. In addition, the existence of other causes of secondary hypertension can also interfere with the interpretation of ARR and thus hamper the diagnosis of PA [ 11 , 12 , 13 ]. Here, we report the first case of a patient with bilateral accessory renal arteries and an aldosterone-producing adenoma.…”
Section: Introductionmentioning
confidence: 99%